Jenis-Jenis Jamur Makroskopis Anggota Kelas Ascomycetes Di Hutan Bayur Kabupaten Landak Kalimantan Barat - Riza Linda, Nina Yuni Tanti, Rahmawati, (Jurnal Protobiont, 2018)
The majority of Ascomycetes is microscopic fungi while only a few are macroscopic ones. Microscopic Ascomycetes function as the decomposer in a forest ecosystem. This study aims to investigate types of Ascomycetes which grow in Bayur Forest, the Regency of Landak, West Borneo. This study has been conducted for four months from March to June 2017. The sample was taken by using Cruise Method. Ascomycetes were identified by matching morphological characteristics of the specimens with the identification book. The collected specimens then were made into wet and dry herbarium. The study shows that Ascomycetes have two Orders. They are Pezizales and Xylariales Orders. Moreover, they comprise three families namely Pyronemataceae, Sarcoscyphaceae and Xylariaceae and consist of six species of Ascomycetes. In addition, Ascomycetes found in Bayur Forest grow mostly on the substrate originated from dead trees.